Ketogenic Diet as Medical Nutrition Therapy - Krishnan, Dharini; Mehndiratta, Chetan; Agrawal, Tanmay (Journal of Social Health and Diabetes, 2019)
Medical nutrition therapy is a therapeutic approach to treat medical conditions and their associated symptoms via using a specifically tailored diet devised under the supervision of a doctor and a registered dietitian or nutrition professional. Ketogenic diet primarily consists of the high amount of fats, a moderate amount of proteins, and very low carbohydrates. It is known to stimulate the metabolic effects of starvation by forcing the body to use primarily fat as a fuel source. Ketogenic diet was developed in the 1920s. Nowadays, it is gaining considerable attention as a potential weight-loss strategy because of the low-carb diet. However, it is being considered for use in several diseases/disorders also because of the beneficial effects on the metabolic health and nervous system. This review revisits the therapeutic potential of ketogenic diets in many pathological conditions and its role as a medical nutrition therapy. It also talks about the ill effects that the keto diet can have in case of self-usage and monitoring.
Keywords: diabetes; ketosis; medical nutrition therapy; ketogenic diet; metabolic health; obesity